Short-term effect of different time interval between self-expanding metallic stent and surgery for left-sided malignant colorectal obstruction - Zhang, Jiawei; Su, Mingli; Lin, Dezheng; Zhong, Qinghua; Hu, Jiancong; Deng, Jiaxin; Lv, Miwei; Xu, Tian; Li, Juan; Guo, Xuefeng (Frontiers in Gastroenterology, 2022)
Abstract Background: The optimal time interval between self-expanding metallic stent (SEMS) placement and surgery in patients with left-sided malignant colorectal obstruction (LMCO) remains controversial. Intestinal obstruction and SEMS placement lead to intestinal edema, local tumor infiltration, and fibrosis, which may have a certain impact on elective surgery. Elective surgery after SEMS placement is disadvantageous and carries a risk of tumor progression, although the time interval between SEMS placement and elective surgery is delayed to 4 weeks. Therefore, our study proposes whether there is a difference in short-term postoperative complication outcomes between waiting for an interval of ≤4weeks compared with an extended interval for neoadjuvant chemotherapy followed by surgery. Methods: All patients who underwent SEMS placement as BTS treatment for LMCO between January 2012 and December 2021 were retrospectively identified. The primary outcomes of this study was short-term clinical postoperative complications (Clavien-Dindo grading ≥II) rate. Results: Of the 148 patients who successfully SEMS for LMCO, 70.27% of patients underwent surgery ≤4 weeks of SEMS placement (Group 1) while 29.73% of patients underwent surgery >4 weeks of SEMS placement (Group 2). The patients in Group 2 who received neoadjuvant chemotherapy and then elective surgery after SEMS placement. Significant differences were observed between both groups for postoperative complications (Clavien-Dindo grading ≥II) (14.4% vs 2.3%, p=0.040), postoperative bowel function time (p<0.001), postoperative hospital stay (p=0.028) and total hospital stay (p=0.002). Conclusions: For the short-term clinical outcome analysis of the interval of elective surgery followed by neoadjuvant chemotherapy after stent placement, is beneficial for postoperative recovery. Therefore, a bridging interval of >4 weeks between SEMS placement and surgery for LMCO is preferable for lower postoperative complication rates and shorter postoperative recovery.